An annotated catalogue and bibliography of the taxonomy, synonymy and distribution of the Recent Vetigastropoda of South Africa (Mollusca) - Herbert, David G. (Zootaxa, 2015)
A complete inventory of the known Recent vetigastropod fauna of South Africa is provided. Bibliographic citations to works discussing the taxonomy, synonymy and distribution of the species in a southern African or south-western Indian Ocean context are provided. Additional explanatory notes are given where pertinent.        New genus records for South Africa: Acremodontina B.A. Marshall, 1995; Choristella Bush, 1879; Cocculinella Thiele, 1909; Conjectura Finlay, 1926; Crosseola Iredale, 1924; Falsimargarita Powell, 1951; Lepetella Verrill, 1880; Profundisepta McLean & Geiger, 1998; Stomatella Lamarck, 1816; Stomatia Helbling, 1779; Stomatolina Iredale, 1937; Synaptocochlea Pilsbry, 1890; Tibatrochus Nomura, 1940; Visayaseguenzia Poppe, Tagaro & Dekker, 2006; Zetela Finlay, 1926.        New species records for South Africa: Acremodontina aff. carinata Powell, 1940; Anatoma finlayi (Powell, 1937); Anatoma munieri (P. Fischer, 1862); Calliotropis acherontis B.A. Marshall, 1979; Calliotropis bucina Vilvens, 2006; Cocculinella minutissima (E.A. Smith, 1904); Diodora ruppellii (G.B. Sowerby (I), 1835); Emarginula costulata Deshayes, 1863; Emarginula decorata Deshayes, 1863; Jujubinus hubrechti Poppe, Tagaro & Dekker, 2006; Lepetella sp.; Seguenzia orientalis Thiele, 1925; Stomatella auricula Lamarck, 1816; Stomatia phymotis Helbling, 1779; Stomatolina angulata (A. Adams, 1850); Stomatolina cf. calliostoma (A. Adams, 1850); Stomatolina aff. danblumi Singer & Mienis, 1999; Stomatolina cf. rubra (Lamarck, 1822); Stomatolina sp.; Synaptocochlea concinna (Gould, 1845); Tectus mauritianus (Gmelin, 1791); Tibatrochus cf. incertus (Schepman, 1908); Turbo imperialis Gmelin, 1791; Turbo tursicus Reeve, 1848; Visayaseguenzia compsa (Melvill, 1904).New species: Spectamen martensi, replacement name for Spectamen semisculptum sensu Herbert (1987) (non Martens, 1904).        New name: Oxystele antoni is proposed as a new name for Trochus (Turbo) variegatus (non Gmelin, 1791 =Heliacus) Anton, 1838.        Revised taxonomy: Cyclostrema semisculptum Martens, 1904 is an earlier name for Solariella intermissa Thiele, 1925, and is referable to the genus Zetela Finlay, 1926; Margarita bicarinata A. Adams & Reeve, 1850 is considered to be a senior synonym of Solariella undata G.B. Sowerby (II), 1870, and is referable to the genus Ilanga Herbert, 1987. Validation of the name Trochus tigrinus Chemnitz, 1781 is credited to Dillwyn (1817) rather than Anton (1838).         New synonyms: Clanculus exquisita Turton, 1932 =Calliostoma africanum Bartsch, 1915; Cyclostrema alfredensis Bartsch, 1915 =Parviturbo alfredensis (Bartsch, 1915); Cynisca gloriosa Bartsch, 1915 =Cinysca spuria (Gould, 1861); Herbertina hayesi Herbert, 1995 =Bruceina chenoderma (Barnard, 1963); Ilanga millardi Herbert, 1987 =Ilanga humillima (Thiele, 1925); Leptothyra africana Bartsch, 1915 =Cinysca spuria (Gould, 1861); Leptothyra albocincta Turton, 1932 =Tricolia striolata (Turton, 1932); Solariella undata G.B. Sowerby (II), 1870, S. gratiosa Thiele, 1925 and S. valdiviae Thiele, 1925 =Ilanga bicarinata bicarinata (A. Adams & Reeve, 1850); Solariella chuni Thiele, 1925, S. intermissa Thiele, 1925, S. gilchristi Barnard, 1963 and S. macleari Barnard, 1963 =Zetela semisculpta (Martens, 1904); Turbo (Collonia) armillatus G.B. Sowerby (III), 1886 =Cinysca spuria (Gould, 1861).        New combinations: Basilissa (Ancistrobasis) compsa Melvill, 1904 is transferred to Visayaseguenzia; Calcar rhysopoma Barnard, 1964 is transferred to Bothropoma; Calliostoma glaucophaos Barnard, 1963 is transferred to Falsimargarita; Calliotropis chenoderma Barnard, 1963 is transferred to Bruceina; Collonia bicarinata Martens, 1902 is transferred to Cinysca; Crossea agulhasensis Thiele, 1925 is transferred to Conjectura; Cyclostrema semisculptum Martens, 1904 is transferred to Zetela; Cyclostremella farica Bartsch, 1915 is transferred to Dikoleps; Cynisca africana Bartsch, 1915 is transferred to Homalopoma; Leptogyra africana: Bartsch, 1915 is transferred to Cirsonella; Leptothyra agulhasensis Thiele, 1925 is transferred to Homalopoma; Leptothyra alfredensis Bartsch, 1915 is transferred to Parviturbo; Leptothyra sola Barnard, 1963 is transferred to a Parviturbo; Liotia (Cynisca) semiclausa Thiele, 1925 is transferred to Cinysca; Monilea spuria Gould, 1861 is transferred to Cinysca; Monodonta gibbula Thiele, 1925 is transferred to Cantrainea; Puncturella voraginosa Herbert & Kilburn, 1986 is transferred to Profundisepta; Solariella fuscomaculata G.B. Sowerby (III), 1892 is transferred to Skenea; Solariella turbynei Barnard, 1963 is transferred to Zetela; Turbo boswellae Barnard, 1969 is transferred to Cantrainea; Turbo foveolatus Barnard, 1963 is transferred to Crosseola; Turbo ponsonbyi G.B. Sowerby (III), 1897 is transferred to Bothropoma; Vitrinella agulhasensis Thiele, 1925 is transferred to Parviturbo; Vitrinella (Docomphala) arifca Bartsch, 1915 is transferred to Lodderena; Vitrinella inclinans Barnard, 1963 is transferred to Skenea.